Phenotypic Expansion in Nasu-Hakola Disease: Immunological Findings in Three Patients and Proposal of a Unifying Pathogenic Hypothesis - Errichiello, Edoardo; Dardiotis, Efthimios; Mannino, Fiorenza; Paloneva, Juha; Mattina, Teresa; Zuffardi, Orsetta (Frontiers in Immunology, 2019)
Nasu-Hakola disease (NHD) is a rare autosomal recessive disorder characterized by progressive presenile dementia and bone cysts, caused by variants in either TYROBP or TREM2. Despite the longly-investigated role of TREM2 and TYROBP/DAP12 in immunity, immunological phenotypes have never been reported in NHD patients. We initially diagnosed by whole-exome sequencing a novel Italian patient with classical NHD clinical sequelae who additionally showed decrease of NK cells and autoimmunity features underlined by the presence of autoantibodies. Based on this finding, we retrospectively explored the immunophenotype in other two NHD patients, in which low NK cell count and positive autoantibody serology were recorded. Accordingly, Trem2-/- mice show abnormal levels of circulating proinflammatory cytokines and dysfunction of immune cells, whereas knockout mice for Tyrobp, encoding the adapter for TREM2, exhibit increased levels of autoantibodies and defective NK cell activity. Our findings tend to redefine NHD as a multisystem “immunological” disease, also considering that osteoclasts are derived from the fusion of mononuclear myeloid precursors, whereas neurological anomalies in NHD are directly caused by microglia dysfunction.